The Investigation of the Charge Transport Properties of Ionic Liquids in Response to Step Voltages in Ionic Polymer Actuators. Issue 1660 (19th August 2014) - Lin, Jun-Hong
ABSTRACT: Developing advanced ionic electroactive devices such as ionic actuators and supercapacitors requires the understanding of charge drifting and diffusion processes, which depends on the distances over which the ions travel. The charge dynamics of Aquivion membrane actuators with EMI-Tf ionic liquid are investigated over a broad film thickness (d) range. A time domain charge dynamic method based on Poisson-Nernst-Planck relation is employed to evaluate the charge transport behaviors in the actuators. It is found that for the initial charging process the double layer time τDL is linearly proportional to the film thickness (d). However, for the later charging process under a high applied voltage (>0.5V ) where the substantial electromechanical reaction occurs, the charge transport behavior does not follow the d 2 dependence as predicted by the random walk diffusion model. For comparison the charge dynamics of BMI-PF6 ionic liquid films without polymer was also investigated.